Density Functional Theory Study of Metal and Metal-Oxide Nucleation and Growth on the Anatase TiO2(101) Surface - Leila Kalantari (MDPI AG, 2021)
Experimental studies have shown the possible production of hydrogen through photocatalytic water splitting using metal oxide (MO<semantics>y</semantics>) nanoparticles attached to an anatase TiO<semantics>2</semantics> surface. In this work, we performed density functional theory (DFT) calculations to provide a detailed description of the stability and geometry of M<semantics>x</semantics>O<semantics>y</semantics> clusters M = Cu, Ni, Co, Fe and Mn, x = 1–5, and y = 0–5 on the anatase TiO<semantics>2</semantics>(101) surface. It is found that unsaturated 2-fold-coordinated O-sites may serve as nucleation centers for the growth of metal clusters. The formation energy of Ni-containing clusters on the anatase surface is larger than for other M clusters. In addition, the Ni<semantics>n</semantics> adsorption energy increases with cluster size n, which makes the formation of bigger Ni clusters plausible as confirmed by transition electron microscopy images. Another particularity for Ni-containing clusters is that the adsorption energy per atom gets larger when the O-content is reduced, while for other M atoms it remains almost constant or, as for Mn, even decreases. This trend is in line with experimental results. Also provided is a discussion of the oxidation states of M<semantics>5</semantics>O<semantics>y</semantics> clusters based on their magnetic moments and Bader charges and their possible reduction with oxygen depletion.